Water crisis and security challenges in the era of climate change - Cindrić, Antonijo; Jovičić, Nives; Skendrović, Kruno (Crisis Management Days, 2025)
The water crisis and climate change are global issues affecting billions of lives on Earth. Extreme weather conditions such as heatwaves, floods, hurricanes, and droughts, resulting from climate change, lead to the extinction of plant and animal species. All these changes drastically alter the supply and quality of drinking water, crucial for agriculture, human consumption, industrial production, and nature conservation. When the supply of drinking or technical water exceeds demand, a water crisis occurs. Hunger, conflicts, diseases, and migrations are possible outcomes of such a crisis. To better cope with climate change and water crises, measures need to be taken at all levels of government, from local to national, as well as internationally. The paper explores the connection between climate change and water crisis and how global warming, precipitation changes, and extreme weather conditions shape the availability and quality of water, especially in arid regions. Special emphasis is placed on the necessity of adaptation and efficient water resource management to mitigate the negative impacts of climate change on water supply, agriculture, ecosystems, and human health. Through concrete examples from different parts of the world, current challenges and approaches to addressing the water crisis in the context of increasingly pronounced climate change are investigated.